Toxicity of pesticides to Chironomus riparius: changes in proteome, biochemical biomarkers and individual responses - Monteiro, Hugo Ricardo Soares (2019)
The application of pesticides in agricultural fields leads to inevitable contamination of adjacent freshwater systems, representing a serious threat to non-target aquatic invertebrate communities. The study of the impact of these stressors on ecologically relevant species is crucial for risk assessment. Traditionally, toxicity testing focuses on organism and population-level responses (e.g. mortality, growth, behavior, and reproduction). However, these responses are often preceded by changes at lower levels of biological organization. In this sense, there is a need to develop sensitive tools that can be used to predict ecological adverse effects of sub-lethal concentrations of pesticides. Assessing sub-organismal endpoints may therefore provide early indicators of pesticide exposure and their possible impacts on natural populations. In this thesis, larvae of Chironomus riparius (Meigen) were exposed to four insecticides with distinct modes of action: amitraz, spinosad, indoxacarb, and fipronil, and their effects evaluated in terms of life-history responses using standard laboratory ecotoxicological tests, and at biochemical level by monitoring specific oxidative stress, neuronal, and energy metabolism biomarkers. Moreover, the effects of spinosad, indoxacarb, and fipronil were assessed at the molecular level using proteomic tools, to determine if proteomics and biochemical biomarkers can be used as reliable and sensitive tools in ecological risk assessment. The results presented here indicate that environmentally relevant concentrations of the insecticides tested can significantly affect several C. riparius life-history traits, with reductions in the larval growth and impairment of emergence endpoints observed for all compounds tested, which ought to compromise the ecological integrity of freshwater ecosystems. At the biochemical level, very distinct responses were observed for each pesticide, probably due to their distinct modes of action. Nonetheless, evidences of high metabolic costs (as indicated by the increase of electron transport system (ETS) and/or lactate dehydrogenase (LDH) activities) were observed for all insecticides, which are probably associated with the activation of antioxidant defenses and detoxification processes. Additionally, evidences of oxidative damage were found in C. riparius larvae under exposure to amitraz and spinosad, as indicated by the increase in lipid peroxidation (LPO) levels. At the proteome level, no significant changes were found in C. riparius proteome between exposed and non-exposed larvae for the concentrations of indoxacarb tested. Fipronil exposure induced alterations in the expression of globins, cytoskeleton and motor proteins, as well as in proteins involved in protein synthesis. Exposure to spinosad resulted in alterations in globins, actin, and cuticle proteins’ expression. These changes observed at the proteome level revealed potential mechanisms of action that lead to the effects observed at the individual level. The potential of C. riparius globins expression in environmental monitoring studies has been previously stated and are here sustained. The generalized downregulation of these proteins observed under exposure to spinosad and fipronil may be related to the toxic effects of these insecticides. This study highlights the importance of complementing standard ecotoxicological approaches with biochemical and molecular tools in an integrative manner. The analyses of biochemical biomarkers and of the proteome can be useful in risk assessment, contributing to the knowledge of the sub-lethal effects of pesticides, thus aiding the comprehensive and mechanistically understanding of the mechanisms that lead to higher level responses. It is also demonstrated that the pesticides tested here pose a potential risk to non-target aquatic invertebrates, and therefore their application near freshwater systems should be reviewed. Chironomus riparius, a model organism in aquatic toxicology, is also presented as a promising model organism for environmental proteomics.